2018
DOI: 10.1142/s0217984918500264
|View full text |Cite
|
Sign up to set email alerts
|

On the paradoxical evolution of the number of photons in a new model of interpolating Hamiltonians

Abstract: We introduce a new Hamiltonian model which interpolates between the Jaynes-Cummings model and other types of such Hamiltonians. It works with two interpolating parameters, rather than one as traditional. Taking advantage of this greater degree of freedom, we can perform continuous interpolation between the various types of these Hamiltonians. As applications we discuss a paradox raised in literature and compare the time evolution of photon statistics obtained in the various interpolating models. The role playe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Luis [8] called such gain of photons a paradoxical phenomenon and showed that a measurement leading to absorption of light produced an increase in the number of photons. Recently, Valverde and Baseia [9] studied the generation of nonclassical states [10] by such paradoxical processes in models of interpolating Hamiltonians, in particular by using nonlinear Jaynes-Cummings interactions. Anaya-Contreras et al [11] have shown that it is possible to deposit several photons in the cavity by passing an atom through it and measuring its state as it exits the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Luis [8] called such gain of photons a paradoxical phenomenon and showed that a measurement leading to absorption of light produced an increase in the number of photons. Recently, Valverde and Baseia [9] studied the generation of nonclassical states [10] by such paradoxical processes in models of interpolating Hamiltonians, in particular by using nonlinear Jaynes-Cummings interactions. Anaya-Contreras et al [11] have shown that it is possible to deposit several photons in the cavity by passing an atom through it and measuring its state as it exits the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Valverde and Baseia [9] studied the generation of nonclassical states [10] by such paradoxical processes in models of interpolating Hamiltonians, in particular by using nonlinear Jaynes-Cummings interactions. Anaya-Contreras et al [11] have shown that it is possible to deposit several photons in the cavity by passing an atom through it and measuring its state as it exits the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Another such interpolation was considered recently. [42] In the present CPB-CQED configuration Fig. 1 we investigate the evolution of the CPB excitation inversion and statistical properties of both subsystems.…”
Section: Introductionmentioning
confidence: 99%